Analisis Kinerja UMKM Mitra Binaan PT. Chevron Pacific Indonesia Dengan Motivasi Usaha Sebagai Variabel Moderasi - Harry Kurniawan; Machasin Machasin; Sakdanur Nas (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
The study was conducted at PT Chevron Pacific Indonesia fostered UMKM in Riau. The aim is to find out the direct effect of work experience, skills and networking on the performance of UMKM with business motivation as a moderation variable. The study took a sample of 70 UMKM. The variables used are experience, skills, Networking, UMKM Performance and Business Motivation as Moderation. Data were analyzed using SEM (Structural Equation Modeling). The results showed that the age of 40-49 years is an age that has a very good income with a value of 4.20. And female sex has a good performance with a value of 4.10. Then the results of the study indicate that there is work participation, skills and networks for the performance of UMKMs. Whereas work experience and skills that are moderated with business motivation do not support UMKM performance. While the network is moderated by motivation to try to the performance of UMKMs